Currents issues in cardiorespiratory care of patients with post-polio syndrome - Marco Orsini; Agnaldo J. Lopes; Fernando S. Guimarães; Marcos R. G. Freitas; Osvaldo J. M. Nascimento; Mauricio de Sant’ Anna Junior; Pedro Moreira Filho; Stenio Fiorelli; Ana Carolina A. F. Ferreira; Camila Pupe; Victor H. V. Bastos; Bruno Pessoa; et al. (Arquivos de Neuro-Psiquiatria)
ABSTRACT Post-polio syndrome (PPS) is a condition that affects polio survivors years after recovery from an initial acute attack of the poliomyelitis virus. Most often, polio survivors experience a gradual new weakening in muscles that were previously affected by the polio infection. The actual incidence of cardiovascular diseases (CVDs) in individuals suffering from PPS is not known. However, there is a reason to suspect that individuals with PPS might be at increased risk. Method A search for papers was made in the databases Bireme, Scielo and Pubmed with the following keywords: post polio syndrome, cardiorespiratory and rehabilitation in English, French and Spanish languages. Although we targeted only seek current studies on the topic in question, only the relevant (double-blind, randomized-controlled and consensus articles) were considered. Results and Discussion Certain features of PPS such as generalized fatigue, generalized and specific muscle weakness, joint and/or muscle pain may result in physical inactivity deconditioning obesity and dyslipidemia. Respiratory difficulties are common and may result in hypoxemia. Conclusion Only when evaluated and treated promptly, somE patients can obtain the full benefits of the use of respiratory muscles aids as far as quality of life is concerned.